Systematic Review of Diarrhea Incidence and Environmental Sanitation - Anissah, Neli (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Toddlers are a highly vulnerable group to diseases transmitted from their surroundings as they are heavily dependent on their parents. Diarrhea remains a global health issue, including in Indonesia. The mortality rate from diarrhea among toddlers remains high in Indonesia, and one of the major risk factors influencing diarrhea in toddlers is environmental sanitation. To identify the potential impact of environmental sanitation on the incidence of diarrhea in toddlers. This research uses a systematic review method by searching literature in various databases. The databases used are Google Scholar, ScienceDirect, PubMed, Scopus, and SpringerLink. The inclusion criteria applied are publications from 2020-2024 and observational study designs. The search identified 17 articles that met the inclusion criteria. Most studies show that sanitation conditions, including toilet cleanliness, access to drinking water, availability of clean water, wastewater management, and waste disposal systems, are associated with the incidence of diarrhea in toddlers. Environmental sanitation plays a crucial role in influencing the occurrence of diarrhea in toddlers. Environmental factors, including toilet conditions, access to clean water, wastewater management, and waste disposal systems, contribute to the risk of diarrhea in toddlers. Additionally, other factors such as handwashing with soap, exclusive breastfeeding, house flooring type, and food and beverage management also play a role in the occurrence of diarrhea. Keywords: Environmental Sanitation, Diarrhea, Toddlers